Cyclone contribution to dust transport over the Mediterranean region. (19th May 2015) - Flaounas, Emmanouil; Kotroni, Vassiliki; Lagouvardos, Konstantinos; Kazadzis, Stelios; Gkikas, Antonis; Hatzianastassiou, Nikolaos
Abstract This study addresses the question of cyclone contribution to dust transport events over the Mediterranean. For this reason, we tracked and associated all intense cyclones in the period 2005–2012 with satellite estimations of the aerosol optical depth, the aerosol index and the aerosol Ångström exponent. Results show that cyclones are related with up to 20% of the total dust events over the Mediterranean, especially affecting its eastern side. When considering only the extreme dust events, the cyclone contribution may reach 70%, highlighting cyclones as one of the main factors for extreme dust transport events in the region.